Fit4CAD: A point cloud benchmark for fitting simple geometric primitives in CAD objects. (February 2022) - Romanengo, Chiara; Raffo, Andrea; Qie, Yifan; Anwer, Nabil; Falcidieno, Bianca
Abstract: We propose Fit4CAD, a benchmark for the evaluation and comparison of methods for fitting simple geometric primitives in point clouds representing CAD objects. This benchmark is meant to help both method developers and those who want to identify the best performing tools. The Fit4CAD dataset is composed by 225 high quality point clouds, each of which has been obtained by sampling a CAD object. The way these elements were created by using existing platforms and datasets makes the benchmark easily expandable. The dataset is already split into a training set and a test set. To assess performance and accuracy of the different primitive fitting methods, various measures are defined. To demonstrate the effective use of Fit4CAD, we have tested it on two methods belonging to two different categories of approaches to the primitive fitting problem: a clustering method based on a primitive growing framework and a parametric method based on the Hough transform. Graphical abstract: Highlights: Fit4CAD, a benchmark for the evaluation of methods for fitting geometric primitives in point clouds. 225 high quality point clouds, 190 of which provided as training set. All models equipped with the list of primitives and their implicit/parametric representations. Two methods to test the benchmark: a primitive growing technique and a parametric surface fitting method. Various criteria to test the benchmark: segmentation quality indicators and primitive approximation accuracy measures.